The Effect Of Applying The Part And Whole Method On Improving Basic Underhand Volleyball Serving Techniques Among Extracurricular Students At Smp Negeri 3 Kota Bengkulu - Novi Lestari (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of the Part and Whole teaching method on improving the underhand serve technique in volleyball among extracurricular students at SMP Negeri 3 Kota Bengkulu. The background of this research is based on the importance of mastering basic techniques in volleyball, particularly the underhand serve, and the need for an appropriate instructional approach for students who have just resumed training after a two-year hiatus. This study employed an experimental method using a one-group pretest-posttest design involving 33 students. Data collection was conducted through skill tests administered before and after the implementation of the Part and Whole method over 16 training sessions. The results showed a significant improvement in students’ underhand serve skills. The average score increased from 7.18 (pretest) to 19.39 (posttest), with a t-count of 24.08 and a p-value of 0.000 (<0.05), indicating that the Part and Whole method had a significant effect on enhancing the underhand serve technique. Therefore, this method can be considered an effective alternative for teaching volleyball skills in extracurricular programs.